2008
DOI: 10.1088/0957-4484/19/29/295708
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical properties of a Ni nanodot-patterned surface

Abstract: Nanomechanical properties of a Ni nanodot-patterned surface (NDPS) on a Si substrate were investigated using nanoindentation. The Ni NDPS was fabricated by thermal evaporation of Ni through a porous anodized aluminum oxide template onto a Si substrate. Plan-view transmission electron microscopy and nanobeam diffraction were used to characterize the Ni nanodot crystal structure. Scanning electron microscopy and atomic force microscopy were used to characterize the morphology and deformation of the Ni nanodots b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 20 publications
0
5
0
1
Order By: Relevance
“…Our study of the mechanical properties of a Ni NDPS showed that the hardness of Ni nanodots on the NDPS is very close to the hardness of nanocrystalline Ni and is much higher than the hardness of microcrystalline and bulk Ni (Wang et al, 2008). The Ni NDPS also showed significant adhesion and friction reduction for potential tribological applications in MEMS (Zou et al, 2006).…”
Section: Introductionmentioning
confidence: 64%
See 3 more Smart Citations
“…Our study of the mechanical properties of a Ni NDPS showed that the hardness of Ni nanodots on the NDPS is very close to the hardness of nanocrystalline Ni and is much higher than the hardness of microcrystalline and bulk Ni (Wang et al, 2008). The Ni NDPS also showed significant adhesion and friction reduction for potential tribological applications in MEMS (Zou et al, 2006).…”
Section: Introductionmentioning
confidence: 64%
“…The material properties used in this study are listed in Table 1. The elastic modulus and yield strength used for Ni were obtained from a previous experimental study of the mechanical properties of a Ni NDPS (Wang et al, 2008). The yield strength of a Ni nanodot was taken as one third of the hardness, which is 2.57 GPa.…”
Section: Results Of Fea Of Single-asperity Contactmentioning
confidence: 99%
See 2 more Smart Citations
“…(11), (12) , ポーラスアルミ ナテンプレートを用いた方法 (13), (14) などが提案されている. これらの方法では, 多数のナノドットを短時間に作製 することが可能であり, 極めて微細なナノドットを得ることができる.…”
Section: やエピタキシャル成長法unclassified